Negotiating the Task of Translation: Modern Orthodox Students Read the Hebrew Bible - Hassenfeld, Ziva R. (Religious education, 2024)
This paper speaks to translation as a powerful window into students’ developing religious literacy practices. It considers how 10- and 11-year-old North American Modern Orthodox Jewish students read and translate the Hebrew Bible refracted through their own cultural and religious expectations: in other words, how students use translation to negotiate their knowledge of biblical Hebrew with their lived experiences of family and gender in the context of modern Jewish life, ritual, and practice. In a Modern Orthodox Jewish school setting, Hassenfeld conducted interviews with 12 students. With each student, she used a task-based interview, asking the students to read and translate a single biblical verse (Genesis 16:15) into English. In completing the translation task, the students applied their technical knowledge of biblical Hebrew and their religious expectations of the ancient text. While translation is perceived in many Modern Orthodox educational contexts as primarily technical (i.e., the precursor to any interpretive activity), this case study suggests that student translation work cannot be separated from interpretive work. While the data set is small and the results only suggestive, the study raises an important theoretical question for future consideration: how can translation be better framed by religious educators who teach sacred texts in their original languages to allow students to understand the necessary interpretive demands it entails?